The effect of manual therapy on lumbar disc protrusion. - Paeslandim, Nadielle de Macedo Rocha; Matos, Ludmilla Karen Brandão Lima de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: A herniated disc is one of the most common diagnoses among the degenerative changes of the lumbar spine. Occurs by a displacement of the nucleus pulposus through the annulus fibrosus and generally postero-lateral lying, may cause compression and irritation of the lumbar roots and dural sac, represented by clinically known as sciatica. Objective: To evaluate the effects of manual therapy on lumbar disc protrusion. Method: The study treated a longitudinal experimental research with quantitative approach. The sample was not random type, consisting of six participants. Pompage, neural mobilization, stabilization, segmental and global postural reeducation: 12 sessions, twice a week, which consisted of the following techniques were performed. Results: The data analyzed in the Graph Pad Prism 5.0 statistical program and the level of significance was p<0,05. In the assessment of the results of the pain Visual Analog Scale, the participants presented a significant decrease. In relation to the neural damage, there was a significant improvement of the test of elevating the leg with the extended knee, but there was not a significant improvement in the Slump Test. In the assessment of the amplitude of the flexion movement of upper body, there was a numerical gain in relation to the flexibility of the patients; however, it was not statistically significant. In the assessment of the variable paravertebral muscular strength, there was a significant improvement. In the abdominal muscular strength, there was a numerical increase; however, this value was not statistically significant. Conclusion: the treatment program with manual techniques used in this present research provided significant effects about the damages caused by lumbar disc protrusion.